APPLICATION OF THE DRILL METHOD TO IMPROVE STUDENT LEARNING OUTCOMES ON FUNERAL PRAYER MATERIALS - Farhan Nurhadi; Abdul Manan; Cut Intan Salasiyah (Journal Informatic, Education and Management (JIEM), 2026)
Factually , students cannot fully develop the thoughts that have been learned in the subject matter , especially in the religious field of funeral prayer material , and when a teacher gives religious education material , the student feels less interested , less motivated to learn or to accept it . As a result , it can reduce the effectiveness of the teaching and learning process . In improving student learning results , the use of the right learning method is required , so that it can improve student learning results in the material taught . Therefore , the researcher raised the problem through a theoretical and empirical approach by using the drill or training method . so the purpose of this research is whether the application of the drill method can improve the learning outcomes of class XI-IA 1 students in the funeral prayer material of SMA Negeri 2 Aceh Barat Daya?. This research uses the Class Level Research (PTK) method which consists of planning , taking action , observing , and reflecting . The subjects in this research are XI-IA class 1 SMA Negeri 2 Aceh Barat Daya students totaling 29 students . Research This is carried out from October -November. This research consists of two cycles , namely data collection done with test and observation techniques . From the results of the test calculation, it is known that the students' knowledge of the field of jurisprudence, especially on the subject of fardhu kifayah about funeral prayer before and after there is an increase in each cycle .